Cementless Tibial Fixation Results in Slower Recovery but Equivalent Outcome at 12 months in Primary Total Knee Arthroplasty - Khairul Anwar Ayob, MSOrth; Ishaan Jagota, BEng; Joshua Twiggs, PhD; David W. Liu, FRACS (Arthroplasty Today)
Background: There is renewed interest in cementless primary total knee arthroplasty (TKA), driven by belief that robotics achieve more precise bone preparation and cementless fixation will improve survivorship, particularly in young patients. We undertook this study to investigate the early recovery trajectory of cementless tibial fixation using a contemporary design in primary TKA. Methods: One hundred and sixty-four propensity score-matched patients who underwent primary TKA with either cemented or reverse hybrid using cementless tibial components were retrospectively analyzed. Knee Injury and Osteoarthritis Outcome Score, Oxford Knee Score, Forgotten Joint Score-12, satisfaction and functional outcome measures including range of motion, sit to stand test, timed up and go, single leg stance, calf raises, and step count were compared between the 2 patient groups during the first 12 months postoperatively. Results: Patients with cemented tibial components had superior Knee Injury and Osteoarthritis Outcome Score scores at 3 and 6 months which was statistically significant. By 12 months, there was no difference in patient-reported outcome measures and overall satisfaction was similar. There was no difference between reverse hybrid and cemented tibial fixation in terms of range of motion and functional outcomes, mean length of stay, complication, blood transfusion, readmission, or reoperation. There were no failures or revisions in either group. Conclusions: Cementless tibial fixation resulted in slower improvement in patient-reported outcome measures during the first 3 to 6 months postoperatively. Patients planned for cementless tibial fixation should be counseled that their recovery may not be as rapid in the first 6 months as cemented fixation.